-(x+8)+9=9x+1-10x

Simple and best practice solution for -(x+8)+9=9x+1-10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+8)+9=9x+1-10x equation:


Simplifying
-1(x + 8) + 9 = 9x + 1 + -10x

Reorder the terms:
-1(8 + x) + 9 = 9x + 1 + -10x
(8 * -1 + x * -1) + 9 = 9x + 1 + -10x
(-8 + -1x) + 9 = 9x + 1 + -10x

Reorder the terms:
-8 + 9 + -1x = 9x + 1 + -10x

Combine like terms: -8 + 9 = 1
1 + -1x = 9x + 1 + -10x

Reorder the terms:
1 + -1x = 1 + 9x + -10x

Combine like terms: 9x + -10x = -1x
1 + -1x = 1 + -1x

Add '-1' to each side of the equation.
1 + -1 + -1x = 1 + -1 + -1x

Combine like terms: 1 + -1 = 0
0 + -1x = 1 + -1 + -1x
-1x = 1 + -1 + -1x

Combine like terms: 1 + -1 = 0
-1x = 0 + -1x
-1x = -1x

Add 'x' to each side of the equation.
-1x + x = -1x + x

Combine like terms: -1x + x = 0
0 = -1x + x

Combine like terms: -1x + x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 37.5(x+400)=6.6666 | | 24x^2-11x-8= | | 6(3y-1)-3(2y)=26 | | 24x^2-10x-8= | | 36+x^2=100 | | -(7-m)=-(5m+7) | | 7(t-2)-t= | | 0=9a^2-4a | | 22x^2-11x-8= | | x^2+2x-4=-2x+1 | | 22x^2-10x-8= | | 22x^2-31x-8= | | -8x-11(x+5)=-2(9x+2) | | x^2+7=1 | | 40x^2+12x-28= | | 40x^2+5x-28= | | 7y+3(y-4)=3(y+1)-2 | | 4x+6=-24 | | -4(t-3)+8t=9t-2 | | -3x+5=-5x-8 | | 2x+7=36 | | 3(x+4)=7x+5-4x+7 | | 3x+12y=12 | | 35+.15m=117.15 | | 49-n^2=0 | | 55-2x=20 | | -5x-21=3x+11 | | x=5-6+-4 | | x^2+10x+38=0 | | 4x+1=-5x+1 | | x=3-6 | | x=3-5 |

Equations solver categories